A Self‐Regulatory Model of Resource Scarcity - Cannon, Christopher; Goldsmith, Kelly; Roux, Caroline (Journal of Consumer Psychology, 2019)
Academics have shown a growing interest in the effects of resource scarcity—a discrepancy between one's current resource levels and a higher, more desirable reference point. However, the existing literature lacks an overarching theory to explain the breadth of findings across different types of resources. To address this, we introduce a self‐regulatory model of resource scarcity. In it, we propose that consumers respond to resource scarcity through two distinct psychological pathways: a scarcity‐reduction route aimed at reducing the discrepancy in resources and a control‐restoration route aimed at reestablishing diminished personal control by attaining security in other domains. We explain how a key determinant of which route the consumer will pursue is the perceived mutability of the resource discrepancy. We also specify moderators, based on our proposed model, to identify when each of the two routes is pursued. This model is assessed in the context of alternative theoretical perspectives, including commodity theory, life history theory, and models of compensatory behavior. Finally, we provide a research agenda for those interested in studying the psychology of resource scarcity from a self‐regulatory perspective.